GAMBARAN KEJADIAN INFEKSI SALURAN KEMIH PADA IBU HAMIL DI BADAN RUMAH SAKIT UMUM TABANAN - Cok Dewi Widhya (Meditory : The Journal of Medical Laboratory, 2018)
Abstract:Background:Urinary tract infection (UTI) is an inflammatory reaction of urothelium cells that line the urinary tract due to the proliferation of microorganisms. During pregnancy, dilatation occurs on the ureter and there is a decrease in ureteral peristalsis which increases the risk of bacterial growth. Aims:The purpose of this study was to determine the incidence of UTI in pregnant women at BRSU Tabanan. Methods:This study was a descriptive study with population of 160 people and sample of 32 people selected by non-probability sampling technique with accidental sampling method.Examination of respondent's urine sample was done by urine culture with standard loop method. Results:The result of this study indicate 19% of pregnant women had calculated colony 105 CFU/ml which can be indicated as UTI.Conclusion:From the result of the study, it was concluded that the incidence of UTI was most prevalent in pregnant women of the age group 20-35 years, pregnant women in the third trimester of pregnancy, in pregnant women with sexual activity 1x/week, in pregnant women with elementary and high school education, and in pregnant women who change underwear twice or more per day and clean the external urinary tract from the front to the back. Keywords :Urinary Tract Infection (UTI), pregnancy